Increasing the capacity of intersections by short traffic lanes - Klibavičius, Antanas; Paliulis, Gražvydas M. (Transport, 2012)
When during peak hours intersections are loaded with 5000÷8000 veh/h, installation of short traffic lanes – one or two in each direction – is one of the most economical solutions for their reconstruction. Technical Construction Regulations (STR 2.06.01:1999) of Lithuania do not provide specific recommendations for calculation of the capacity of short traffic lanes. During 2005–2010, the authors of the article performed on-site tests of transport flows in the city of Vilnius and devised the methodology for modelling and calculation of short traffic lane capacity considering the size of the traffic flows. The article presents recommendations on calculation of lost time and vehicle queue lengths considering the size of traffic flows.First Published Online: 30 Mar 2012